ACTION OF VARIOUS STEROIDS ON ISCHEMIC STRIATED MUSCLE - TELLEZ GARCIA, DOLORES; PARDO, EFRAIN G (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1941)
The action of diosgenin, digitonin, desoxycholic acid, ergosterol, pregnenolone, progesterone, testosterone, estradiol, and desoxycorticosterone acetate was studied on ischemic striated muscle Ergosterol and testosterone produced an improvement in muscul
CIENC MEX
Keywords: ACTION, VARIOUS, STEROIDS, ISCHEMIC, STRIATED, MUSCLE; CIENCIAS MEDICAS; FARMACOLOGIA